Invasive Pulmonary Aspergillosis with Disseminated Infection in Immunocompetent Patient - Gabriel Moreno-González; Antoni Ricart de Mesones; Rachid Tazi-Mezalek; Maria Teresa Marron-Moya; Antoni Rosell; Rafael Mañez (Canadian Respiratory Journal)
Invasive pulmonary aspergillosis (IPA) is a rare pathology with increasing incidence mainly in critical care settings and recently in immunocompetent patients. The mortality of the disease is very high, regardless of an early diagnosis and aggressive treatment. Here, we report a case of a 56 yr old previously healthy woman who was found unconscious at home and admitted to the emergency room with mild respiratory insufficiency. In the first 24 hours she developed an acute respiratory failure with new radiographic infiltrates requiring Intensive Care Unit admission. A severe obstructive pattern with impossibility of ventilation because of bilateral atelectasis was observed, requiring emergent venovenous extracorporeal membrane oxygenator device insertion. Bronchoscopy revealed occlusion of main bronchi, demonstrating by biopsy an invasive infection by Aspergillus fumigatus and A. flavus. Despite an aggressive treatment and vital support the patient had a fatal outcome. The forensic study confirms the diagnosis of IPA but also revealed the presence of disseminated aspergillosis.